2013
DOI: 10.1021/jp402051t
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic Carbon–Water Nonbonded Interaction Parameters

Abstract: In this study, we develop graphitic carbon-water nonbonded interaction parameters entirely from ab initio calculation data of interaction energies between graphene and a single water molecule. First, we employ the Møller-Plesset perturbation theory of the second order (MP2) method to compute the polycyclic aromatic hydrocarbon (PAH)-water interaction energies, with proper size of basis sets and energy component analysis to extrapolate to infinite-sized graphene limit. Then, we develop graphitic carbon-water in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
201
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(221 citation statements)
references
References 95 publications
16
201
0
1
Order By: Relevance
“…77 Moreover, recent theoretical work has suggested that graphitic surfaces are intrinsically hydrophilic. 66,67,179 In the current work, spectroscopic ellipsometry results on fresh G/Cu further support this conclusion.…”
Section: Gomez-herrero Et Al Reported Aromatic Hydrocarbon Contaminasupporting
confidence: 80%
“…77 Moreover, recent theoretical work has suggested that graphitic surfaces are intrinsically hydrophilic. 66,67,179 In the current work, spectroscopic ellipsometry results on fresh G/Cu further support this conclusion.…”
Section: Gomez-herrero Et Al Reported Aromatic Hydrocarbon Contaminasupporting
confidence: 80%
“…The van der Waals interaction parameters between carbon and water were taken from Wu and Aluru. 28 Simulations were performed using the GROMACS 4.6 software package. 33 Details of the simulation can be found in Reference 28. are most likely due to differences in HOPG sample characteristics (e.g., orientation, purity, cleavability, grain size etc.)…”
Section: Methods A3-cleaving In Uhp Argon Followed By Wca Measurement mentioning
confidence: 99%
“…The intrinsic value of WCA is a critical parameter that can be used to validate the simulated interaction of water molecules with the graphene surface for different applications, including separation and sensing. 12,28 The main objectives of this work were to measure the intrinsic wettability of the clean The following methods were used to measure the intrinsic WCA of HOPG by mechanical cleavage; to measure WCA in a contaminant-free environment; and to clean the HOPG surface by using different thermal annealing, ion bombardment, and chemical treatment methods ( Figure 1). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ...…”
Section: Introductionmentioning
confidence: 99%
“…This has involved a very broad range of approaches, such as periodic quantum Monte Carlo, random phase approximation calculations, coupled cluster, and symmetry adapted perturbation theory on acene clusters. Wu, Aluru and co--workers tabulated many of the results (157), and although a consensus has yet to be reached, these high--level calculations yield values in the 70--120 meV range (~ 2--4 kcal/mol). In desalination studies, it is necessary to also describe ion--water and ion--ion interactions.…”
Section: Frontiers Of Simulation Studiesmentioning
confidence: 99%